PENERAPAN STRATEGI BAURAN PEMASARAN UNTUK MENINGKATKAN JUMLAH PESERTA ASURANSI (STUDI PT ASURANSI JIWA SYARIAH AL AMIN KEDIRI): PENERAPAN STRATEGI BAURAN PEMASARAN UNTUK MENINGKATKAN JUMLAH PESERTA ASURANSI (STUDI PT ASURANSI JIWA SYARIAH AL AMIN KEDIRI) - Sulistiawati, Sulistiawati; MADYASARI, ARLUPI (Syar'Insurance: Jurnal Asuransi Syariah, 2023)
Marketing strategy is a form of planning a business to achieve its goals with optimal results. In the world of insurance, competition is something that needs to be considered, especially in the field of marketing, marketing is the most important factor that greatly influences the performance of an insurance institution. insurance institutions must hold promotional communications to prospective customers, because this is the key to success in providing products or services to prospective customers. The research method used in this journal is a qualitative research method. In this study using descriptive research type. The marketing strategy implemented by PT Asuransi Jiwa Syariah Kediri is a marketing mix strategy consisting of product strategy, price strategy, location strategy, promotion strategy, service strategy, process strategy, service people/officers, and physical evidence support strategy. PT. Al Amin Kediri Sharia Life Insurance in increasing the number of participants The highest percentage increase for 3 years in 2022 is 37% then the smallest percentage in 2020 is 18%. Increase from 2020 to 2021 by 7%, from 2021 to 2022 by 12%. The table above shows that the increase in the number of insurance participants occurred at Al Amin, but this still did not meet the target of Al Amin because the planned target was around 50%. This was because at that time the marketing mix had already been implemented at PT Asuransi Jiwa Syariah Al Amin Kediri. but the implementation has not been 100% done because there are obstacles in the implementation of the 7p marketing mix